Spiritualitas Kehidupan Orang Percaya dalam Menantikan Kedatangan Kristus Kedua Kali (Eskatologi) - Elisabet Elisabet; Wilna Repelita; Wandi Wandi; Hendro Sarmauli; Sarmauli Sarmauli (Jurnal Magistra, 2024)
The teaching of Christian eschatology emphasizes the importance of understanding future events revealed through prophecy. Bible prophecy is the center of study in eschatology, which serves as a fundamental doctrine that needs to be taught in churches, families, and Christian religious education in schools. This teaching is important to guide students in understanding the meaning of repentance and faith in Jesus Christ as the way of salvation for eternal life. Through eschatological understanding, students are invited to prepare themselves spiritually with the belief that Jesus will come the second time to gather believers. In the first stage of resurrection, both Old and New Testament believers, as well as the living, will experience rapture to heaven with glorified bodies. Christian religious education in schools should teach students to be vigilant, work faithfully, develop skills, and understand responsibility for their actions. As such, eschatology provides the glorious hope of the Lord's return, shaping the character and spirituality of believers.